ANOMALIES OF THE ISOSTATIC KURIL-OKHOTSKK REGION - Stroev P.A.; Romashova O.N. (My University, 1992)
The map is presented of isostatic gravity anomalies in the south part of the Sea of Okhotsk and Kuril Island arc-trench system. Lines of equal anomalies are drawn through 20 mgal. The normal gravitational formula is the International Cassinis formula, 1930. The isostatic anomalies are explained by the inner structure of the crust, lithosphere and asthenosphere. They indicate the considerable density inhomogeneity of the earth crust and upper mantle. A map of the average 1°×1° isostatic anomalies is also given.